The impact of COVID-19 Standard Operating Procedure for businesses on job stress and job performance in lodges and homestays of Sukau, Kinabatangan / Boyd Sun Fatt ... [et al.] - Sun Fatt, Boyd; Jailani, Sylviana Imelda; Daniel, Shareen Dina; Hong, Leanne Marian; Kibat, Silverina Anabelle; Bidder, Christry; Mogindol, Spencer Hedley; Aidi, Muhammad Zulhazmi (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
COVID-19 pandemic has left accommodation business operators with no choice and they had to implement all the provided guidelines. They also need to brief their employees to ensure that they adhered to the SOP as new norms of business. To date, there is limited literature that examine the connection between SOP, job stress and job performance during a pandemic. Considering the research gap, this research aimed to investigate the level of stress among the operators and their employees in implementing the new norms brought about by COVID-19 working SOP. It specifically studied lodges and homestays around Sukau, Kinabatangan. The job stress and work performance served as a guide in the study to ascertain the findings. A total of 10 questionnaires were distributed to homestay operators and their employees. The data was analysed using quantitative and qualitative methods. Findings from the analysis revealed that for most of the operators and employees, job stress is low, but the job performance is high. Based on the findings, several suggestions were made to reduce job stress and increase job performance. Several limitations of the study were also highlighted that should serve as signpost for future research.